Influence of sequential inoculum of Starmerella bacillaris and Saccharomyces cerevisiae on flavonoid composition of monovarietal Sangiovese wines. Issue 9 (17th June 2020) - Mangani, Silvia; Buscioni, Giacomo; Guerrini, Simona; Granchi, Lisa
Abstract: The selection of Starmerella bacillaris strains to be used with Saccharomyces cerevisiae as mixed cultures has been recently suggested in order to produce wines containing lower ethanol and higher glycerol concentrations and to promote fructose degradation due to their fructophilic character. However, studies about effects of such mixed starter cultures on phenolic compounds, which are responsible for the colour and health‐enhancing properties in red wines, are currently lacking. Therefore, in this work, the influence of sequential inoculated fermentation (SIF) with Starm. bacillaris and S. cerevisiae on phenolic content of monovarietal Sangiovese wine was evaluated by fermentations at laboratory scale. Axenic fermentations (AXFs) with S. cerevisiae were performed as control. S. cerevisiae attained higher cell densities in AXF compared with SIF. The experimental wines obtained by SIF showed significant lower ethanol and higher glycerol concentrations, whereas no significant difference was detected in colour intensity. The total phenol index reached significantly lower values in SIF. Furthermore, the wines produced by SIF contained higher concentrations of vitisin A that has a greater colour stability than the anthocyanin monomer. Finally, a lower content of both free anthocyanins and flavan‐3‐ols, key compounds for wine quality possessing also health‐enhancing properties, was found in wines obtained by SIF. On the contrary, no significant difference was detected on flavonol concentration between SIF and AXF. This study highlighted that the use of sequential inoculum of Starm. bacillaris and S. cerevisiae can contribute to increasing the colour stability of red wines, even if at the expense of compounds with health properties.